(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The initial (initial) planning consists of developing the main directions of forecasting, target parameters of financial activities, the strategy of the entity’s general financial activities, and implementing them through the parameters and objectives of current financial planning. In turn, the foundations of current financial planning should be developed and communicated to the budgets that directly implement all aspects of the entity’s financial activities.